Dysregulated MicroRNA Expression and Chronic Lung Allograft Rejection in Recipients With Antibodies to Donor HLA. Issue 7 (3rd February 2015) - Xu, Z.; Nayak, D.; Yang, W.; Baskaran, G.; Ramachandran, S.; Sarma, N.; Aloush, A.; Trulock, E.; Hachem, R.; Patterson, G. A.; Mohanakumar, T.
<x xml:space="preserve">Abstract</x> The pathogenesis of chronic rejection, Bronchiolitis Obliterans Syndrome (BOS) following lung transplantation (LT) is poorly understood. We hypothesized that development of antibodies to HLA (DSA) is associated with dysregulation of microRNA (miRNA) that predisposes BOS. Towards this, miRNA profiling of mononuclear cells from 10 stable LT (DSA−BOS−), 10 LT with DSA+BOS− (DSA group) and 10 LT with DSA+BOS+ (BOS group) were performed. Prediction by mirPath indicated that differential miRNAs in DSA+BOS− compared to stable are significantly up‐regulated (relative fold >2, p < 0.05) for TGF‐β and B cell receptor signal pathways. A total of seventy‐four miRNAs were up‐regulated and six miRNAs were down regulated in LT with DSA+BOS+ when compared to stable (relative fold >2, p < 0.05). There was also significant enrichment of cell cycle and gap junction pathways. An inverse correlation between expression of two key miRNAs and their target genes were observed: miR‐369‐5p and miR‐548d were down regulated in DSA+ LT while their gene targets in TGF‐β signal pathways were up‐regulated. In addition, miR‐628‐5p and miR‐134 were down regulated and their target genes (B cell development) were up‐regulated. Therefore, we conclude that alloimmunity induced changes in miRNAs affecting the TGF‐β and B cell receptor signal pathways play important roles in BOS development.